2023
DOI: 10.3390/w15040668
|View full text |Cite
|
Sign up to set email alerts
|

Decision Support for Lake Restoration: A Case Study in Swedish Freshwater Bodies

Abstract: A considerable number of lakes in Sweden have high phosphorus internal loading from the sediments which cause cyanobacterial blooms every summer. Due to potential risks with such blooms for human health, drinking water supply, and ecosystem services, measures need to be taken to control the phosphorus content. Measures to control the phosphorus input from the surrounding land has been in focus. However, the measures have not been sufficient. This is because phosphorus deposited at the bottom of the lakes for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The management and control of eutrophication and algae in water sources should consider water usage safety and the ecological risks associated with chemical and microbial methods of algae control, which are challenging to manage. In the prevention and control of algae in water sources such as lakes and reservoirs, the focus should be on reducing nutrient sources, particularly internal sources within the reservoir, and implementing biological and physical algae control measures, such as ecological fish stocking, mollusk breeding, and algae removal equipment [51][52][53][54][55].…”
Section: Simulation Scenariosmentioning
confidence: 99%
“…The management and control of eutrophication and algae in water sources should consider water usage safety and the ecological risks associated with chemical and microbial methods of algae control, which are challenging to manage. In the prevention and control of algae in water sources such as lakes and reservoirs, the focus should be on reducing nutrient sources, particularly internal sources within the reservoir, and implementing biological and physical algae control measures, such as ecological fish stocking, mollusk breeding, and algae removal equipment [51][52][53][54][55].…”
Section: Simulation Scenariosmentioning
confidence: 99%
“…In some urban lakes, however, in‐lake chemical treatments were determined to be more cost effective than catchment measures as the costs for reducing external loads sufficiently to improve water quality would be extreme (Huser, Futter, et al, 2016). In a recent study, aluminum treatment was identified as an optimal approach to reduce the internal P load in two Swedish lakes because this treatment combined the highest internal load reduction efficacy with the lowest cost (Sellergren et al, 2023). For Spring Lake (USA) however, Steinman (2019) concluded that, while alum reapplication may be the most cost‐effective solution for aesthetics, it does not lead to ecosystem restoration in a holistic sense because the method creates a vicious cycle of enrichment and treatment and releases potential polluters from responsibility.…”
Section: Implementing the Framework Of Sustainable Lake Restorationmentioning
confidence: 99%
“…The paper "Decision Support for Lake Restoration: A Case Study in Swedish Freshwater Bodies" [7] presents techniques aimed at providing decision support for lake restoration through a combination of multi-criteria analysis and decision analysis. The main objective is to identify effective and efficient measures for restoring lakes.…”
Section: Overview Of the Contributions Of This Special Issuementioning
confidence: 99%
“…On the other hand, among nine research articles, five articles are related to water quality problems, of which two articles investigate groundwater pollution in Japan and Sweden [5,6], one article deals with lake contamination by phosphorus in Sweden [7], another targets lakes or reservoirs from the perspective of the hydrodynamic response by wind [8], and the last one considers the water pollution problem for a riverbank area in Bangladesh [9]. Three research articles out of the nine are related to problems of urban flood phenomena, in which studies on urban flooding area characteristics in Japan [10], water level forecasting caused by urban floods in Japan [11], and barriers to IFRM (Integrated Flood Risk Management) adaptation in the Philippines [12] are carried out.…”
Section: Introductionmentioning
confidence: 99%